Disorders of water-electrolyte metabolism in pulmonary edema under inhibition of the renin-angiotensin-aldosterone system - Tiupka, T. I.; Zalyubovska, O. I.; Zlenko, V. V.; Avidzba, Yu. N.; Litvinenko, M. I.; Minaieva, A. O. (Journal of Education, Health and Sport, 2018)
The aim of the study was to study the disorders of water-electrolyte metabolism in pulmonary edema under conditions of inhibition of RAAS by ACE inhibitors. Studies were performed on 70 white rats weighing 160-180 gon two models of pulmonary edema: hemodynamic (adrenaline) and acute toxic. In rats with hemodynamic pulmonary edema the pulmonary coefficient increased 3.3 times as compared with the intact control, where it was 0.68 %. With acute toxic edema, this indicator also increased, but to a lesser extent – 2.4 times. We established that the minute diuresis in animals with hemodynamic pulmonary edema decreased by 1.9 times, and with acute toxic edema – by 1.5 times. There was also a decrease in the concentration of sodium in the urine in groups of animals with hemodynamic edema and with acute toxic edema in 1.5 and 1.3 times, respectively. The use of ACE inhibitors for pulmonary edema leads to a decrease in the degree of their hyperhydration and normalization of water-electrolyte homeostasis. Compared with enalapril, zofenopril had a more pronounced anti-edematous effect in both hemodynamic and acute toxic edema of the lungs.